(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Vegetables are considered as a commercially important and nutritionally important food commodity due to its major dietary source of vitamins, sugars, organic acids and minerals. The topic of loss reduction in vegetables is the challenge to meet the requirements of future generation. This loss reduction can be expressed as post-harvest losses occurring in vegetables. “Post-harvest loss” is the term used to describe the crops lost to waste, spoilage, and other factors between harvest and consumption by the end user. This article summarizes the literature on various techniques to reduce or prevent post-harvest losses and to increase its shelf life.